Lutein attenuates diabetic-induced renal damage via inhibiting oxidative and nitrosative stresses - Fatani, Amal J.; Al-Rejaie, Salim S.; Parmar, Mihir Y.; Ahmed, Omer M.; Abuohashish, Hatem M.; Ahmed, Mohammed M. (Progress in Nutrition, 2017)
Diabetic nephropathy is a complex disease that involves production of free radicals, which are strongstimulus for pro-inflammatory factors. Present study was designed to explore the potential alleviating effects of lutein against streptozotocin-induced diabetic renal oxidation, inflammation and apoptosis in rats. Lutein was supplemented with diets content in three different doses (40, 80 and 160 mg/kg diets). Levels of glucose, albumin, creatinine and urea were determined in serum and urine. Renal expression of pro-inflammatory cytokines, nucleic acids and caspase-3 activity were estimated and also the kidney levels of thiobarbituric acid reactive substances (TBARS), total and non-protein sulfhydryl groups (T-SH and NP-SH), nitric oxide (NO) and inducible nitric oxide synthase (iNOS) along with superoxide dismutase (SOD) and catalase (CAT) activities. Renal histopathological features were analyzed. The diabetic animals showed apparent alterations in serum and urine biochemistry and also demonstrated evident elevated renal levels of pro-inflammatory mediators and apoptosis. Measured oxidative/nitrosative stress biomarkers were found altered markedly in the renal tissues of diabetic rats. Lutein supplementation to the diabetic animals significantly improved serum and urinary biochemistry. In renal tissue, the altered pro-inflammatory cytokines, nucleic acids and caspase-3 activity were ameliorated following lutein supplementation. Diabetic animals supplemented with lutein exhibited normal values of TBARS, T-SH, NP-SH and iNOS as well as SOD and CAT activities particularly in higher dose. Histological analysis further confirmed lutein’s renal protective effects. These results demonstrated clear evidence that lutein offered a significant protective effect against diabetes-induced nephrotoxicity by inhibiting the oxidative and nitrosative process in renal tissue.